Ga-68- and Cu-64-Labeled NOTA-Albumin Conjugates for PET Sentinel Lymph Node Imaging. (18th February 2013) - Schiller, Eik; Bergmann, Ralf; Wunderlich, Gerd; Andreeff, Michael; Jacob, Anita; Pietzsch, Hans-Jürgen
Abstract : Our objective was to develop and evaluate Ga-68- and Cu-64-labeled albumin conjugates for PET imaging of sentinel lymph nodes. Four different albumin conjugates were prepared starting from NOTA-HSA. The lymph node uptake of Ga-68- and Cu-64-labeled albumin conjugates was investigated after subcutaneous injection into the foot pad of Wistar rats. A pig model was utilized for further biological evaluation of the lymph node uptake. For all the four conjugates, radiolabeling with Ga-68 and Cu-64 resulted in >95% radiochemical yield. Denatured and mannosylated Ga-68 NOTA-HSA revealed the highest popliteal lymph node uptake in rats (2.78% ± 0.38 % ID and6.13% ± 1.13 % ID 10 min and 60 min p.i., resp.). The popliteal lymph node reached its maximum activity after approximately 120 min and remained constant for denatured and mannosylated Cu-64 NOTA-HSA at least up to 240 min p.i. In a pig model, 2% of the injected dose of this compound was found in the sentinel lymph node 60 min after subcutaneous injection. In conclusion, PET imaging of sentinel lymph nodes with Ga-68- and Cu-64-labeled denatured NOTA-Man-HSA could be successfully demonstrated and deserves further investigations.